Acute and chronic effect of sodium bicarbonate ingestion on Wingate test performance: a systematic review and meta-analysis - Lopes-Silva, J. P.; Reale, R.; Franchini, E. (Journal of Sports Sciences, 2019)
The aim of this study was to perform a systematic review and meta-analysis on the acute and chronic effects of sodium bicarbonate (NaHCO3) ingestion on Wingate performance. Following a search through PubMed, Scopus and Web of Science, 9 studies were found meeting inclusion criteria (6 acute and 3 chronic). Random-effects meta-analysis of standardized mean difference (SMD) for peak and mean power was performed. Study quality was assessed using the QualSyst. Results of the meta-analysis showed that acute ingestion of NaHCO3 did not improve Wingate test peak (weighted average effect size Hedges`s g = 0.02, 95%CI: - 0.19 to 0.23, P = 0.87) or mean power (weighted average effect size Hedges`s g = 0.15, 95%CI: -0.06 to 0.36, P = 0.92). However, chronic ingestion of NaHCO3 improved Wingate test peak (weighted average effect size Hedges`s g = 1.21, 95%CI: 0.83 to 1.42, P = 0.001) and mean power (weighted average effect size Hedges`s g = 1.26, 95%CI: 0.96 to 1.56, P = 0.001). Quality assessment of selected articles was classified as strong. This meta-analysis provides evidence that chronic, but not acute, ingestion of NaHCO3 increases both Wingate test peak and mean power.